Pengaruh Fundamental Makro, Struktur Modal, Struktur Kepemilikan, Kinerja Keuangan, Karakteristik Perusahaan dengan GCG sebagai Variabel Moderasi terhadap Nilai Perusahaan pada Perusahaan Sub Sektor Pertambangan yang Terdaftar di BEI - Sullicyanna Luna Bianca; Hwihanus Hwihanus (Akuntansi, 2024)
This study aims to analyze the effect of macro fundamentals, capital structure, ownership structure, financial performance, company characteristics, with good corporate governance as a moderating variable on firm value. This study uses quantitative methods with secondary data types, namely annual reports. The population of this study is all mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2020 - 2022 with a total research sample of 13 companies selected using purposive sampling method. Data processing and analysis techniques using SMART-PLS software version 2. The results of this study indicate that macro fundamentals, capital structure, and ownership structure have no significant effect on firm value while financial performance and company characteristics have a significant effect on firm value; macro fundamentals have a significant effect on capital structure; macro fundamentals and capital structure have no significant effect on ownership structure; macro fundamentals have no significant effect on financial performance while capital structure has a significant effect on financial performance; macro fundamentals and capital structure have no significant effect on company characteristics; ownership structure and company characteristics have no significant influence on financial performance; with GCG moderation ownership structure and financial performance have a significant effect on firm value while company characteristics have no significant effect on firm value.